Mind the Gap: The expectation and reality of involved fatherhood - Machin, A (Men's Studies Press, 2015)
It is now the expectation within the UK that fathers will be actively involved in the birth and care of their offspring; they will be “involved fathers”. However, studies have shown that a gap exists between this expectation and the reality. Using qualitative and quantitative techniques this study aims to explore the reasons for this disparity by documenting the experiences of 15 first-time fathers over an 8 month period from 7 months gestation to 6 months post-birth. Analysis of questionnaire and interview data produces five key themes which give insight into some of the reasons for the gap: the role of the father, bonding and co-parenting, experience of the National Health Service (NHS) and father wellbeing, work life and government and society. While fathers are keen to fulfil the role of the involved father they are prevented from fulfilling this desire by societal attitudes, issues relating to the development of their baby, economic barriers, a lack of support from healthcare practitioners and government policies which do not provide realistic prospects for fathers to be involved. Fathers experience considerable tension when trying to balance their desire to be involved with their baby with the economic necessity to work. This situation is exacerbated by a lack of targeted support. Implications for future practice are considered.